A Kinematic Analysis of the star excursion balance test and its ability to predict Injury - Hoosen, Taskeen (My University, 2018)
Background Recent studies have shown an increase in incidence and prevalence of injury in cricket. Successful injury prevention requires ongoing injury surveillance and injury screening for early intervention of at risk players. Objective The aims of this study are to determine if the Star Excursion Balance Test (SEBT) and 3D kinematics of the lower limb are predictive of lower limb injury in cricket and to determine the lower limb kinematics during the SEBT. Method This is an observational, longitudinal cohort study. Twenty-four provincial level adult male cricket players participated in this study. Pre-season questionnaires were completed for baseline information and to determine eligibility. Participants performed the SEBT while being analysed by Optitrack 3D kinematics cameras and software. Injury surveillance took place during the 2015/2016 cricket season with injury monitoring questionnaires. Statistical test including correlations, tests for significance, a receiver operating curve and regression analyses were all performed, in order to establish if there is a relationship between the SEBT, 3D kinematics and injury prediction. Results Twenty-two participants with a mean age of 20.2 (SD= 3.8) completed the study. 50% sustained injuries; 59% of which were in the lower limb. Lumbar injuries were the most prevalent. There were no statistically significant results between the injured and non-injured groups during the SEBT. Regression analysis revealed decreased hip flexion angles of the stance leg in the anterior direction accurately predict 76% likelihood of injury. The ankle abduction angle was statistically significant when comparing injured and non-injured participants in the anterior direction of both limbs (Dominant p= 0.035; Non-Dominant p= 0.022) and in the postero-lateral direction of the dominant limb (p= 0.035). Knee abduction angles were statistically significant when comparing injured and non-injured participants in the postero-medial direction in the non-dominant limb (p= 0.008). Conclusion The SEBT in its simplest form did not predict an increased risk of injury. Supplemented with the hip, knee and ankle angular kinematics, the findings of the SEBT were able to predict injury.
‘A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Physiotherapy” Johannesburg 2018.
Keywords: Star Excursion Balance Test (SEBT); Injury Prediction; Leg Injuries; Lower Extremity